Tuning the emission of aqueous Cu:ZnSe quantum dots to yellow light window. (8th July 2015) - Wang, Chunlei; Hu, Zhiyang; Xu, Shuhong; Wang, Yanbin; Zhao, Zengxia; Wang, Zhuyuan; Cui, Yiping
Abstract: Synthesis of internally doped Cu:ZnSe QDs in an aqueous solution still suffers from narrow tunable emissions from the blue to green light window. In this work, we extended the emission window of aqueous Cu:ZnSe QDs to the yellow light window. Our results show that high solution pH, multiple injections of Zn precursors, and nucleation doping strategy are three key factors for preparing yellow emitted Cu:ZnSe QDs. All these factors can depress the reactivity of CuSe nuclei and Zn monomers, promoting ZnSe growth outside CuSe nuclei rather than form ZnSe nuclei separately. With increased ZnSe QD size, the conduction band and nearby trap state energy levels shift to higher energy sites, causing Cu:ZnSe QDs to have a much longer emission.